Isoform-specific knockdown and expression of adaptor protein ShcA using small interfering RNA. - Kisielow, Malgorzata (2002)
Many eukaryotic genes are expressed as multiple isoforms through the differential utilization of transcription/translation initiation sites or alternative splicing. The conventional approach for studying individual isoforms in a clean background (i.e. without the influence of other isoforms) has been to express them in cells or whole organisms in which the target gene has been deleted; this is time-consuming. Recently an efficient post-transcriptional gene-silencing method has been reported that employs a small interfering double-stranded RNA (siRNA). On the basis of this method we report a rapid alternative approach for isoform-specific gene expression. We show how the adaptor protein ShcA can be suppressed and expressed in an isoform-specific manner in a human cell line. ShcA exists in three isoforms, namely p66, p52 and p46, which differ only in their N-terminal regions and are derived from two different transcripts, namely p66 and p52/p46 mRNAs. An siRNA with a sequence shared by the two transcripts suppressed all of them. However, another siRNA whose sequence was present only in p66 mRNA suppressed only the p66 isoform, suggesting that the siRNA signal did not propagate to other regions of the target mRNA. The expression of individual isoforms was achieved by first down-regulating all isoforms by the common siRNA and then transfecting with an expression vector for each isoform that harboured silent mutations at the site corresponding to the siRNA. This allowed functional analysis of individual ShcA isoforms and may be more generally applicable for studying genes encoding multiple proteins.